Metabolic modulation of neuronal gamma-band oscillations - Vodovozov, Wadim; Schneider, Justus; Elzoheiry, Shehabeldin; Hollnagel, Jan-Oliver; Lewen, Andrea; Kann, Oliver (Pflügers Archiv, 2018)
Gamma oscillations (30-100 Hz) represent a physiological fast brain rhythm that occurs in many cortex areas in awake mammals, including humans. They associate with sensory perception, voluntary movement, and memory formation and require precise synaptic transmission between excitatory glutamatergic neurons and inhibitory GABAergic interneurons such as parvalbumin-positive basket cells. Notably, gamma oscillations are exquisitely sensitive to shortage in glucose and oxygen supply (metabolic stress), with devastating consequences for higher cognitive functions. Herein, we explored the robustness of gamma oscillations against changes in the availability of alternative energy substrates and amino acids, which is partially regulated by glial cells such as astrocytes. We used organotypic slice cultures of the rat hippocampus expressing acetylcholine-induced persistent gamma oscillations under normoxic recording conditions (20% oxygen fraction). Our main findings are (1) partial substitution of glucose with pyruvate and the ketone body β-hydroxybutyrate increases the frequency of gamma oscillations, even at different stages of neuronal tissue development. (2) Supplementation with the astrocytic neurotransmitter precursor glutamine has no effect on the properties of gamma oscillations. (3) Supplementation with glycine increases power, frequency, and inner coherence of gamma oscillations in a dose-dependent manner. (4) During these treatments switches to other frequency bands or pathological network states such as neural burst firing or synchronized epileptic activity are absent. Our study indicates that cholinergic gamma oscillations show general robustness against these changes in nutrient and amino acid composition of the cerebrospinal fluid; however, modulation of their properties may impact on cortical information processing under physiological and pathophysiological conditions.
Gesehen am 26.03.2019